2013
DOI: 10.1126/scitranslmed.3006597
|View full text |Cite
|
Sign up to set email alerts
|

PD-1– and CTLA-4–Based Inhibitory Chimeric Antigen Receptors (iCARs) Divert Off-Target Immunotherapy Responses

Abstract: T cell therapies have demonstrated long-term efficacy and curative potential for the treatment of some cancers. However, their use is limited by damage to bystander tissues, as seen in graft-versus-host disease after donor lymphocyte infusion, or “on-target, off-tumor” toxicities incurred in some engineered T cell therapies. Non-specific immunosuppression and irreversible T cell elimination are currently the only means to control such deleterious responses, but at the cost of abrogating therapeutic benefits or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
500
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 619 publications
(506 citation statements)
references
References 57 publications
(89 reference statements)
4
500
0
2
Order By: Relevance
“…Based on the modular composition of the prototype CAR, the intracellular activating domain can be exchanged by a moiety which delivers inhibitory signals to the T cell, including PD-1, CTLA-4, or CD45 [63]. Such an inhibitory CAR (iCAR) represses T cell activation upon binding to cognate antigen (Figure 1).…”
Section: Cars Providing Inhibitory Signals: Icarsmentioning
confidence: 99%
“…Based on the modular composition of the prototype CAR, the intracellular activating domain can be exchanged by a moiety which delivers inhibitory signals to the T cell, including PD-1, CTLA-4, or CD45 [63]. Such an inhibitory CAR (iCAR) represses T cell activation upon binding to cognate antigen (Figure 1).…”
Section: Cars Providing Inhibitory Signals: Icarsmentioning
confidence: 99%
“…A group at the Memorial Sloan-Kettering Cancer Center thinks it has solved the problem with T cells expressing two antigenspecific receptors to distinguish on-target cancer cells from off-target normal cells. 1 Chimeric antigen receptor (CAR) T cells currently in the clinic are made up of an antigen-specific single-chain variable fragment (scFv) fused to T cell-activating and -co-stimulatory domains. The CAR is designed to bind to an extracellular, tumor-associated antigen, and the stimulatory domains cause T cells to activate and proliferate, thus eliminating tumor cells.…”
mentioning
confidence: 99%
“…However, when they traffic to the tumor environment with availability of only aCAR, but not iCAR antigen, CAR-T cells can be fully activated to elicit antitumor immunity. 41 Other elegantly designed logic-gate T cells have also been reported and some of them also require dual antigen recognition for CAR-T activation. 36,37 Our mCAR method offers one more strategy to create conditionally active CARs for enhancing tumor-specificity of CAR-T cells with less structural complexity.…”
mentioning
confidence: 99%
“…[36][37][38][39][40][41] One elegant strategy exploits dual targeting with two CARs to achieve selective recognition of tumor, but not normal cells. Sadelain and co-workers 38 demonstrated that T cells expressing two CARs targeting two different antigens could operate as logic gates to control full T cell activation.…”
mentioning
confidence: 99%